Analisis Efisiensi Dan Produktivitas Industri Besar Dan Sedang Di Wilayah Provinsi Bali (Pendekatan Stochastic Frontier Analysis) - Pratiwi, Ayu Manik; Bendesa, I K G; Yuliarmi, N (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 1, Februari 2014 (pp. 1-82)DO - 10.24843/JEKT.2014.v07.i01.p08)
The aim of this research is to determine the performance of large and medium industries, including the level of technical efficiency, the elasticity of output to input, and find sources of growth in Total Factor Productivity (TFP) of large and medium industries in the province of Bali in 2001-2010. Analytical techniques used in this study is the Stochastic Frontier Production Function using translog function approach with variable time. The results showed that the variables of labor and raw materials significantly influence the output. The level of technical efficiency from year to year has decreased, and not all large and medium industrial classification in the province of Bali has been streamlined in full. Elasticity of output to input level is the largest output elasticity of inputs. And sources of TFP growth in the province of Bali is dominated by scale components and technological changes so that the improvement in the business climate as well as production facilities and infrastructure is expected to increase TFP growth is still considered low.
Keywords: Stochastic Frontier , Technical Efficiency , Total Factor Productivity Growth